2023
DOI: 10.5603/fm.a2022.0023
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatization of the articular eminence in cone-beam computed tomography: prevalence and characteristics — literature review

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Since the diagnosis of ZACD usually occurs indecently, understanding the prevalence of ZACD is essential for clinicians and researchers alike, as its diagnosis is crucial for surgical operations [ 11 ]. The ZACD increases the risk of perforation and complications during eminectomy and eminoplasty [ 16 , 17 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the diagnosis of ZACD usually occurs indecently, understanding the prevalence of ZACD is essential for clinicians and researchers alike, as its diagnosis is crucial for surgical operations [ 11 ]. The ZACD increases the risk of perforation and complications during eminectomy and eminoplasty [ 16 , 17 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have recorded a high variability of the ZACD prevalence ranging from 1 to 76.7% due to the differences in the geographical regions, imaging modalities used for assessment, and age range included in the study [ 9 11 ]. On the other hand, most studies focused on adults [ 12 – 19 ] or a wide age range for both children and adults [ 20 24 ] following the concept derived from previous studies [ 2 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High pneumatization is also considered a predisposing factor [3,65] (Figure 13); however, confirming this assertion in the present analysis was not possible owing to the lack of objective data. A recent review on pneumatization of the articular eminence [120] showed that the overall prevalence of articular tubercle pneumatization was 25.22% (n = 6393, women: 25.14%, men: 25.81%), showing no correlation between the frequency, location, or type of pneumatization and the age or sex of the patient. The average minimum thickness of the glenoid fossa roof was approximately 0.8 mm and was not significantly correlated with sex, age, or mandibular head morphology [121,122].…”
Section: Diagnosis Of the Condyle And Glenoid Fossamentioning
confidence: 99%